Manfaat Terapi Tambahan Vitamin pada Pasien Nyeri Neuropati Diabetika - Asisaratu, Edenia; Pinzon, Rizaldy Taslim; Pramudita, Esdras Ardi (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023, 2023)
Background: Painful Diabetic Neuropathy is one of the most common complications of Diabetes Mellitus, which becomes a burden that necessitates optimal treatment. Current treatment is symptomatic therapy with glycemic index control but it has yet to reach the best results. Supplementing with vitamins B and D has been shown to provide significant pain relief in previous studies. Methodology: This was a retrospective cohort study. A total of 107 subjects were sampled using consecutive sampling method and they were given either symptomatic therapy or symptomatic therapy plus vitamins for three months. The pain scale was measured using Neuropathic Pain Scale. Results: The subjects were compared in three comparison groups. Subjects who received symptomatic therapy plus vitamin had the greatest pain reduction (39,50±14,222) (p=0,000) in the first comparison group. Subjects who received symptomatic therapy plus vitamin B combination and vitamin D 1000 IU had the greatest pain reduction (53,00±6,749) (p=0,000) in the second comparison group. Subjects who received symptomatic therapy plus vitamin D 1000 IU had the greatest pain reduction (44,00±8,944) (p=0,088) in the third comparison group. Conclusions: Additional vitamin therapy resulted in a significantly greater pain reduction than symptomatic therapy alone. There was no significant difference in pain reduction between the vitamin D 400 IU addition and vitamin D 1000 IU addition. Keywords: painful diabetic neuropathy; pain intensity; vitamin B; vitamin D